Chimeric antigen receptor T-cell as a significant player in the innovative treatment of hematological cancers - Karolina Makowska; Kinga Panuciak; Angelika Mastalerczyk; Emilia Nowicka; Michał Obel; Kamila Czyżak; Jan Lejman; Natalia Trąbka; Klaudia Jedlina; Katarzyna Pacek (Kazimierz Wielki University, 2023)
Introduction and purpose: Chimeric antigen receptor‐T (CAR‐T) cells have achieved inspiring outcomes in the treatment for lymphoid malignancies, especially diffuse large B-cell lymphoma (DLBCL) and acute lymphoblastic leukemia (ALL), providing alternative therapeutic options for patients who failed to respond to conventional treatments. CAR-T are based on the patient's T lymphocytes, which through genetic modification, gain new abilities to detect and fight cancer cells. Although the percentage of complete remissions after standard treatment of B-cell malignancies is quite high, methods that could have an even better result regarding patient survival by reducing the side effects of treatment are still being sought to improve the quality of patients' lives. CAR-T is a culmination of many years of research in the dynamically developing area of immunotherapy as a revolutionary therapy of hematological cancers treatments. State of knowledge: In order to explore the topic, analysis included research available in the PubMed database. The research focused on the possibility of using CAR-T cell therapy in selected hematological cancers. Conclusion: CAR-T is one of the most advanced and personalized methods of immunotherapy. Despite the side effects of this method, there is still scope for improvement. Our overview summarizes all the issues that have been overcome in designing this therapy, as well as highlighting all the challenges that still need to be addressed.